تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر -دراسة ميدانية للجمعيات والنوادي الرياضية بولاية المسيلة-. - تومي ، نصرالدين; Supervisor : بوصلاح ، النذير (Mohamed Boudiaf University of M'Sila, 2025)
الملخص : بالعربية: تضمنت الدراسة موضوع بعنوان " تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر، وكانت الدراسة ميدانية بالجمعيات والنوادي الرياضية بالمسيلة ،حيث هدفت الدراسة الى معرفة درجة مساهمة حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر، وللتحقق من صحة الفرضيات تم اعتماد المنهج الوصفي التحليلي، حيث تمثل مجتمع البحث في رؤساء وأمناء المال للأندية والجمعيات بالمسيلة، قام الباحث باختيار عينة البحث بالطريقة العشوائية البسيطة، والبالغ قوامها 200 فردًا، بنسبة 32.25%من المجتمع الأصلي المتجانس والبالع عدده 620 فردًا، حيث تم استرجاع 192 استمارة، وقمنا بتصميم استمارة الاستبيان كأداة للدراسة ، قد توصلت الدراسة إلى أن تطبيق حوكمة التسيير المالي يمكن أن يسهم بدرجة كبيرة في تحسين إدارة الجمعيات والنوادي الرياضية في الجزائر من خلال زيادة الشفافية والمساءلة في استخدام الموارد المالية،.وبفضل سياسة ترشيد النفقات، يمكن تحسين استخدام الأموال وتوجيهها نحو الأولويات الأساسية بطريقة أكثر فعالية، ومن خلال الامتثال للقوانين واللوائح المحلية المتعلقة بإدارة الجمعيات والنوادي الرياضية، يساعد هذا في تقديم تقارير مالية دقيقة وفقًا للمعايير المحلية والدولية، مما يزيد من مصداقية الجمعيات والنوادي أمام المانحين والجمهور، هذا كله لا يأتي إلا من خلال وجود هيكل تنظيمي جيد وفعال حيث يتطلب وجود إدارة كفؤة للوصول إلى الهدف المرجو. الكلمات المفتاحية:حوكمة،التسيير المالي،إدارة، الجمعيات والنوادي الرياضية، سياسة ترشيد النفقات. عنوان الدراسة : تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر أهداف الدراسة :  ستحاول هذه الدراسة تحقيق هدف رئيسي وهو معرفة درجة مساهمة تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر.  التعرف على دور الجانب القانوني في تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر.  التعرف على دور الهيكل التنظيمي في تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر.  التعرف على دور وظيفة تسيير وإدارة الموارد المالية في تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر. التساؤل العام الدراسة : ما درجة مساهمة تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر؟. التساؤلات الجزئية : 1- هل الجانب القانوني يعمل على تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر؟ 2- هل الهيكل التنظيمي يساعد على حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر؟ 3- هل وظيفة تسيير وإدارة الموارد المالية تعمل على حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر؟ الفرضية العامة للدراسة : يساهم تطبيق حوكمة التسيير الماليبدرجة كبيرة في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر الفرضيات الجزئية 1- الجانب القانوني يعمل على تطبيق حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر. 2- الهيكل التنظيمي يساعد على حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر. 3- وظيفة تسيير وإدارة الموارد المالية تعمل على حوكمة التسيير المالي في إدارة الجمعيات والنوادي الرياضية في ظل سياسة ترشيد النفقات بالجزائر. المنهج المتبع في الدراسة :................... المنهج الوصفي التحليلي......................... الأدوات المستخدمة في الدراسة :.....................الاستبيان.............................. الكلمات المفتاحية: بالعربية: حوكمة،التسيير المالي،إدارة، الجمعيات والنوادي الرياضية، سياسة ترشيد النفقات. بالإنجليزية governance, financial management, management, sports associations and clubs, expenditure rationalization policy جاء هذا البحث في فصول . الفصل الأول:......................... الإطار العام للدراسة......................... وتناول الفصل الثاني:............. الحوكمة والقانون................................ أما الفصل الثالث..................... التسيير المالي في ظل سياسة ترشيد النفقات.......... الفصل الرابع:.................... إدارة الجمعيات والنوادي الرياضية...................... الفصل الخامس: منهجية الدراسة الفصل السادس: عرض وتحليل ومناقشة النتائجا الفصل السابع :الاستنتاجات والاقتراحات من أهم النتائج التي توصل إليها الباحث : 1- إن حوكمة التسيير المالي تلعب دوراً حيويًا في تحسين إدارة الجمعيات والنوادي الرياضية في الجزائر، خاصة في سياق سياسة ترشيد النفقات، من خلال الجوانب القانونية، الهيكل التنظيمي، ووظيفة تسيير الموارد المالية. 2- تطبيق حوكمة التسيير المالي يمكن أن يسهم في تحسين إدارة الجمعيات والنوادي الرياضية في الجزائر من خلال زيادة الشفافية والمساءلة في استخدام الموارد المالية. هذا يعني أنه بفضل سياسة ترشيد النفقات، يمكن تحسين استخدام الأموال وتوجيهها نحو الأولويات الأساسية بطريقة أكثر فعالية. 3- الجانب القانوني يساهم في تطبيق حوكمة التسيير المالي، مما يعزز الامتثال للقوانين واللوائح المحلية المتعلقة بإدارة الجمعيات والنوادي الرياضية. هذا يساعد في تقديم تقارير مالية دقيقة وفقًا للمعايير المحلية والدولية، مما يزيد من مصداقية الجمعيات والنوادي أمام المانحين والجمهور. 4- الهيكل التنظيمي الجيد يعزز حوكمة التسيير المالي بتحديد الأدوار والمسؤوليات بشكل واضح، وضمان تقديم التقارير المالية في الوقت المناسب وبدقة. بفضل سياسة ترشيد النفقات، يمكن تخصيص الموارد بشكل فعال داخل الجمعيات والنوادي، مما يعزز من قدرتها على تحقيق أهدافها بكفاءة أكبر. 5- تسهم وظيفة تسيير وإدارة الموارد المالية في تطبيق حوكمة التسيير المالي من خلال إدارة الإيرادات والنفقات بطريقة مستدامة وفعالة، مما يضمن استدامة الجمعيات والنوادي على المدى الطويل. بفضل سياسة ترشيد النفقات، يتم تعزيز إدارة الموارد المالية لتلبية احتياجات الأعضاء والمجتمع بشكل أفضل. أهم التوصيات: إنشاء سياسات وإجراءات مالية شفافة يسهل على الجميع فهمها واتباعها، ونشر تقارير مالية منتظمة وعلنية لتمكين الجميع من الاطلاع على الوضع المالي. تحديد مسؤوليات وصلاحيات واضحة ضمن الهيكل التنظيمي، وتوفير تدريب مستمر للموظفين والمسؤولين عن الإدارة المالية لتحسين مهاراتهم وكفاءتهم. التأكد من أن جميع العمليات المالية تتماشى مع القوانين واللوائح الوطنية والدولية، وإنشاء وحدة داخلية لمراقبة الامتثال والتأكد من تنفيذ القوانين واللوائح. وضع خطط مالية واستراتيجية طويلة المدى لتحقيق الاستدامة المالية، وتطوير ميزانيات سنوية تشمل جميع الأنشطة والنفقات المتوقعة، وإجراء تحليل دوري للوضع المالي والتكيف مع التغيرات الاقتصادية والمالية. Searchlight in English Faculty Institute of Sciences and Sports and Technical and PhysicalActivities Department: Order No:......................................................... No. d 'registration : ...................... D.AGS/3C/06/21................. ...................... Searcher : ............................ .......Toumi Nasreddine............................................ Publicly supported on :.....................30/01/2025........................................... Title of the thesis (dissertation Applying financial management governance in associationmanagementand sports clubs in light of the policy of rationalizing expenses in Algeria -A field study of sports associations and clubs in the state of M'Sila- Language of the thesis: .......................Arabic................................................... Model of the thesis: ...........Doctorat.... ................................................................ Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor : Bouslah Nadir Grade: Lecturer Number of pages: ...................................198.. ................. Summary: The study included a topic entitled “Applying financial management governance in the management of associations and sports clubs in light of the policy of rationalizing expenses in Algeria. The study was a field study in sports associations and clubs in M’sila, where the study aimed to know the degree of contribution of financial management governance in the management of associations and sports clubs in light of the policy of rationalizing expenses in Algeria.” To verify the validity of the hypotheses, the descriptive analytical approach was adopted, where the research community was represented by the presidents and treasurers of the clubs and associations in M’sila. The researcher selected the research sample in a simple random way, which consisted of 200 individuals, representing 32.25% of the original homogeneous and comprehensive community of 620 individuals, where 192 questionnaires were retrieved, and we designed the questionnaire form as a tool for the study. The study concluded that applying financial management governance can contribute significantly to improving the management of associations and sports clubs in Algeria by increasing transparency and accountability in the use of financial resources. Thanks to the policy of rationalizing expenses, The use of funds can be improved and directed towards key priorities in a more effective manner. By complying with local laws and regulations related to the management of associations and sports clubs, this helps in providing accurate financial reports in accordance with local and international standards, which increases the credibility of associations and clubs before donors and the public. This is all possible. Except through the presence of a good and effective organizational structure, as it requires efficient management to reach the desired goal. Title of the study:.. Applying financial management governance in associationmanagementand sports clubs in light of the policy of rationalizing expenses in Algeria -A field study of sports associations and clubs in the state of M'Sila- The purpose of the study The study aims to achieve a main objective, supported by the following specific goals, all related to the management of sports associations and clubs in Algeria under the policy of expenditure rationalization: 1. To determine the extent of the contribution of applying financial management governance to the administration of sports associations and clubs in Algeria, particularly under the policy of expenditure rationalization. 2. To identify the role of the legal aspect in the application of financial management governance in the management of sports associations and clubs in Algeria under the policy of expenditure rationalization. 3. To identify the role of the organizational structure in the application of financial management governance in the management of sports associations and clubs in Algeria under the policy of expenditure rationalization. 4. To identify the role of the financial resource management function in the application of financial management governance in the management of sports associations and clubs in Algeria under the policy of expenditure rationalization. Problem: General Question What is the degree of contribution of applying financial management governance to the administration of sports associations and clubs in Algeria, considering the current policy of expenditure rationalization? Specific Questions 1. Does the legal framework facilitate the application of financial management governance in the administration of sports associations and clubs in Algeria, considering the policy of expenditure rationalization? 2. Does the organizational structure aid the implementation of financial management governance in the administration of sports associations and clubs in Algeria, considering the policy of expenditure rationalization? 3. Does the financial resource management function contribute to the implementation of financial management governance in the administration of sports associations and clubs in Algeria, considering the policy of expenditure rationalization? Hypotheses: General Hypothesis The application of financial management governance contributes significantly to the administration of sports associations and clubs in Algeria, particularly under the current policy of expenditure rationalization. Sub-Hypotheses 1. The legal framework facilitates the application of financial management governance in the administration of sports associations and clubs in Algeria under the policy of expenditure rationalization. 2. The organizational structure aids the implementation of financial management governance in the administration of sports associations and clubs in Algeria under the policy of expenditure rationalization. 3. The function of financial resource management promotes the implementation of financial management governance in the administration of sports associations and clubs in Algeria under the policy of expenditure rationalization. Key words : governance, financial management, management, sports associations and clubs, expenditure rationalization policy - The most important results achieved are: Establish transparent financial policies and procedures that are easy for everyone to understand and follow, and publish regular and public financial reports to enable all stakeholders to review the financial situation. Define clear responsibilities and authorities within the organizational structure, and provide continuous training for employees and officials responsible for financial management to enhance their skills and competence. Ensure that all financial operations are in compliance with national and international laws and regulations, and establish an internal compliance monitoring unit to ensure the implementation of all laws and regulations. Develop long-term financial and strategic plans to achieve financial sustainability, formulate annual budgets that include all expected activities and expenditures, and conduct periodic analysis of the financial situation to adapt to economic and financial changes.
Keywords: :حوكمة; التسيير المالي; إدارة; الجمعيات والنوادي الرياضية